Boron-based hydrogen storage materials for highly selective conversion to liquid organic hydrogen carriers synthesis focus on formic acid - Ulgen, Berfin Ekin; Filiz, Bilge Coskuner; Acikalin, Korkut; Yoruklu, Hulya Civelek; Figen, Aysel Kanturk (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Recent progress in synthesizing liquid organic hydrogen carriers (LOHCs) using conversion technology has shown that boron-based materials have significant potential as hydrogen storage materials. Here, we present the production of LOHCs, focused on formic acid (HCOOH) through conversion methodology. To achieve this objective, we directly supply hydrogen from boron-based materials (sodium borohydride-NaBH4, potassium borohydride-KBH4, and ammonia borane-NH3BH3) in the reaction medium for LOHCs sythesis. We carefully examined how reaction parameters (such as pH, temperature, and flow rate) affect the efficiency (E, %) of boron-based hydrogen storage materials using Central Composite Design (CCD). We found that the optimal conversion conditions were 50 degrees C, 0.7 M NaBH4, and 60 mL/min gas flow, resulting in a maximum E (87%). The results demonstrate the production of HCOOH with excellent product selectivity (PS,>94%) using NaBH4 as a hydrogen source.
Keywords: Boron-based; Hydrogen storage; Liquid organic hydrogen carrier; Formic acid; Hydrogenation; CARBON-DIOXIDE; CO2 HYDROGENATION; CATALYTIC-HYDROGENATION; REDUCTION; METHANOL; SODIUM; BOROHYDRIDE; HYDROBORATION; NANOPARTICLES; FORMATE; Chemistry; Electrochemistry; Energy & Fuels